Fostering socio-emotional competencies in children on the autism spectrum using a parent-assisted serious game: A multicenter randomized controlled trial. (May 2022) - Kirst, Simone; Diehm, Robert; Bögl, Katharina; Wilde-Etzold, Sabine; Bach, Christiane; Noterdaeme, Michele; Poustka, Luise; Ziegler, Matthias; Dziobek, Isabel
Abstract: Objective: Serious games are a promising means of fostering socio-emotional skills in children on the autism spectrum (AS). However, empathy and related constructs have not yet been addressed comprehensively and together with emotion recognition, and there is a lack of randomized controlled trials (RCT) to investigate skill maintenance and the transfer to functional behavior. Method: The manualized, parent-assisted serious game Zirkus Empathico (ZE) was tested against an active control group, in a six-week multicenter RCT. Eighty-two children aged 5–10 years on the AS were assessed at baseline, post-treatment, and three-month follow-up. Empathy and emotion recognition skills were defined as the primary outcomes. The secondary outcomes included measures of emotional awareness, emotion regulation, autism social symptomatology (Social Responsiveness Scale), and subjective therapy goals. Results: Training effects were observed after the intervention for empathy ( d = 0.71) and emotion recognition ( d = 0.50), but not at follow-up. Moderate effects on emotional awareness, emotion regulation, and autism social symptomatology were indicated by the short and mid-term assessments. Parents reported treatment goal attainment and positive training transfer. Conclusion: While a six-week training with ZE failed to induce lasting changes in empathy and emotion recognition, it may be effective for improving emotional awareness and emotion regulation, and mitigate general autism symptomatology. Clinical trial registration information: Zirkus Empathico – Promoting socioemotional competencies in 5- to 10-year-old children with autism spectrum conditions using a computer-based training program; https://www.drks.de/ ; DRKS-ID: DRKS00009337; Universal Trial Number (UTN): U1111-1175-5451. Highlights: Parent-assisted serious game for children on the autism spectrum tested in 6-week multicenter RCT. Training effects post-treatment for empathy and emotion recognition. Moderate effects on emotional awareness and emotion regulation also at 3-months follow-up. Autism social symptomatology improved in short- and mid-term assessment. High treatment satisfaction, acceptance, and training transfer in parental report.